Anomalous behavior detection using Spatio temporal Feature and 3D CNN model for Surveillance - Nahar, Jannatun; Promi, Zarin Tasnim; Ferdous, Jannatul; Ishrak, Fatin; Khurshid, Ridah (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.